There's no place like OM: Vesicular sorting and secretion of the peptidylarginine deiminase of Porphyromonas gingivalis. Issue 1 (1st January 2018) - Gabarrini, Giorgio; Palma Medina, Laura M.; Stobernack, Tim; Prins, Rianne C.; du Teil Espina, Marines; Kuipers, Jeroen; Chlebowicz, Monika A.; Rossen, John W. A.; van Winkelhoff, Arie Jan; van Dijl, Jan Maarten
ABSTRACT: The oral pathogen Porphyromonas gingivalis is one of the major periodontal agents and it has been recently hailed as a potential cause of the autoimmune disease rheumatoid arthritis. In particular, the peptidylarginine deiminase enzyme of P. gingivalis (PPAD) has been implicated in the citrullination of certain host proteins and the subsequent appearance of antibodies against citrullinated proteins, which might play a role in the etiology of rheumatoid arthritis. The aim of this study was to investigate the extracellular localization of PPAD in a large panel of clinical P. gingivalis isolates. Here we show that all isolates produced PPAD. In most cases PPAD was abundantly present in secreted outer membrane vesicles (OMVs) that are massively produced by P. gingivalis, and to minor extent in a soluble secreted state. Interestingly, a small subset of clinical isolates showed drastically reduced levels of the OMV-bound PPAD and secreted most of this enzyme in the soluble state. The latter phenotype is strictly associated with a lysine residue at position 373 in PPAD, implicating the more common glutamine residue at this position in PPAD association with OMVs. Further, one isolate displayed severely restricted vesiculation. Together, our findings show for the first time that neither the major association of PPAD with vesicles, nor P. gingivalis vesiculation per se, are needed for P. gingivalis interactions with the human host.